India's Principal Scientific Advisor reviews evidence-based advice on climate-smart, sustainable practices - CGIAR Research Program on Wheat (2021)
Recent policy report with recommendation submitted to the Principal Scientific Adviser of India: “Agricultural Policies and Action-Plans for a Secure and Sustainable Agriculture."